(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Laser surgery is a surgical procedure in which tissue is cut with a laser (laser scalpel) instead of a traditional scalpel. The laser beam vaporizes the water in the soft tissue and then cuts it. It is often used in eye surgery, where the laser has become one of the most promising weapons for surgeons and dermatologists. . Lasers can be used in many surgical procedures, including laser resurfacing. The laser resurfacing process is important as it vaporizes the surface layers on the skin and thus contributes to removing wrinkles and lines resulting from sunlight. The laser beam also has a natural sterilizing effect that vaporizes bacteria, viruses, and fungi, leading to a reduction in local infections. Perhaps most importantly, the laser reduces post-operative pain by blocking the nerve endings